Marketing accountability and excellence in the Portuguese state school: The construction of school social image through academic performance - Leonor Lima Torres; José Augusto Palhares; Almerindo Janela Afonso (Arizona State University, 2018)
The authors seek to establish a relationship between the results of standardised tests, the academic excellence and the corresponding form of accountability. This relationship adopts the idea that standardised tests and academic excellence sustain not only a model of managerial accountability, but a (quasi) market model of accountability in education as well, providing school marketing schemes. This study is supported by a long-term fieldwork developed in several Portuguese state schools, where we analysed main documents, observed the public rituals of academic distinction, interviewed the principals and teachers and surveyed students. The results show us that these public rituals are part of a marketing strategy that helps to build a good school image, essential to induce the school choice by families and to reinforce the decisions of the principal's leadership.